The Interpretation of UNCITRAL Law in Australian Courts: A Roadmap for Elevating the UN Sales Convention’s Status to That of Arbitration Law - Hayward, Benjamin (Sydney Law Review, 2025)
Despite being part of Australian law for more than 30 years, the United Nations Convention on Contracts for the International Sale of Goods (‘CISG’) has not secured the internationally minded interpretation that CISG art 7(1) requires. Australia’s international commercial arbitration (‘ICA’) laws, however, are routinely approached by Australian courts with an internationalist perspective, as their own interpretative rules require. It is tempting to conclude that Australia’s approach to interpreting its ICA laws is transferable to the CISG context. In this article I address a previously unexplored nuance affecting that conclusion. Australian courts routinely accept Singaporean, Hong Kong and New Zealand interpretative influence concerning ICA laws. In the CISG context, however, significantly less influence from those jurisdictions exists. That being so, I explore how Australia’s courts might better apply the CISG in an internationalist manner. First, I recommend that Australia’s courts emphasise to practitioners the need to consider the CISG’s application and its internationalist interpretation requirements. Second, I recommend that Australian courts use the amicus curiae procedure to solicit third party submissions addressing the CISG’s interpretation. Both techniques are applied by foreign courts in the ICA context and would assist Australian courts in discharging their CISG art 7(1) obligations.
Keywords: Asia-Pacific; Australia; CISG; Harmonisation; International commercial arbitration; Model Law; New York Convention; Sales law; Statutory interpretation

The role of ADR and judicial agreements: legal analysis and behavioral economics insights - Solano Mantilla, Valeria (LUISS Guido Carli, 2025)
From rationality to reality. The evolution of law and economics through the behavioral lens. Understanding how we choose: foundations of behavioral economics. Rethinking law through the lens of behavioral economics. Why law needs behavioral economics. The challenge of integrating behavioral economics into private law: freedom vs regulation. The double-edged sword of behavioral economics: protecting consumers from psychological manipulation. Balancing innovation and consumer rights: a global view on consumer protection in the EU, Italy and Colombia. Alternative dispute resolution and the judicial agreements. The justice system seen though behavioral economics. Judicial agreements: procedural autonomy and enhancing judicial cooperation. Alternative dispute resolution (ADR) and mediation: legal frameworks, party autonomy and behavioral economic. A brief comparative analysis on mediation: EU, Italy and Colombia. Applying behavioral economics in the ADR (mediation).
Keywords: ADR; Alternative dispute resolution; Economic behaviour; Mediation; Médiation

Transparency in Investor-State Arbitration Under USMCA - Petrova Georgieva, Virdzhiniya (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
The provisions of USMCA and their interpretation and application in the developing case law of international arbitral tribunals constituted under its investment chapter show a progressive move towards a higher transparency standard in the resolution of inves-tor-State disputes. The incorporation of most of the UNCITRAL Rules on Transparen-cy in USMCA Annex 14-D expanded the scope of NAFTA’s transparency rules. The entry into force of USMCA and the recent end of NAFTA’s “legacy claims” is to bring normative uniformity across the case law of arbitral tribunals on issues of procedural transparency. In addition, better access to arbitral orders and awards under USMCA will promote the quality of the decisions, as tribunals and parties will be able to lean on the experience of their predecessors. Las disposiciones del T-MEC y su aplicación en la jurisprudencia arbitral internacional muestran un avance hacia mayores estándares de transparencia en disputas inversionista-Estado. Al incorporar la mayoría de las Reglas de Transparencia de la CNUDMI en su Anexo 14-D, el T-MEC amplió el marco del TLCAN. La entrada en vigor del T-MEC y el fin de las “reclamaciones heredadas” del TLCAN promueven una mayor uniformidad normativa en torno a la transparencia procesal. Esta coherencia fortalecerá la aceptación del capítulo de inversión del T-MEC y aumentará la legitimidad del arbitraje de inversiones a nivel global.
Keywords: Arbitraje internacional de inversiones; Arbitrajes entre Inversionistas y Estados; CNUDMI; International Investment Arbitration; NAFTA; Procedural transparency; T-MEC; TLCAN; Transparencia procedimental; UNCITRAL Rules on Transparency; USMCA

Promoting Treaties in Nigeria and Operationalising the Singapore Convention on Mediation - Okoli, Pontian (African Journal of Legal Studies, 2025)
In Nigeria, the United Nations Convention on International Settlement Agreements Resulting from Mediation (2018) has entered into force. This Convention was incorporated or domesticated by referring to it in the Arbitration and Mediation Act (2023), but statutes are often dedicated to the domestication of treaties. There is no consensus on the most pragmatic way(s) to facilitate Nigerian treaty engagement. This article examines the Nigerian legal regime on treaties and explores the extent to which the regime can be maximised considering the Vienna Convention on the Law of Treaties (1969). A case is made for a principled basis to underpin the domestication of treaties that facilitate international business, including dispute resolution treaties. This analytical basis should enable legislative flexibility already woven into the overarching legal regime. The article articulates how such flexibility can be used to promote the operationalisation of relevant treaties using the Arbitration and Mediation Act as a paradigm.
Keywords: Good faith; International commercial mediation; Legislative flexibility; Singapore Convention; Treaties; Vienna Convention

International Arbitration: Impact on Global Economy - Jahan, Bushrat (International Journal of Innovation and Applied Studies, 2025)
The significant increase in the development of world economy over the last few decades have been experienced a considerable increase in the number of commercial disputes. When there is any business and dealings with contracts the question of dispute must be happened. But all of the parties actually want to run their business well and smoothly. In recent world a massive part of global economy depends on the trans-border business. But disputes in such business dealings sometimes can be the reasons to become risk the inter-relation of those parties. Which can affect the global economy as a whole. Comparing to the disputes inside domestic entities the trans-border or international business disputes can arise as bigger problem because of different jurisdictions, diverse legal systems and tradition. International Court of Justice (ICJ) already has the jurisdiction to try all the international civil suits but Alternative Dispute Resolution (ADR) mechanism also considered as a viable alternative to resolve the dispute over the court. The international arbitration arises as a way of alternative dispute resolution mechanism which upraise benefits both of the parties and maintain the confidentiality. In this paper details of international arbitration and the broader impact of this mechanism in the global business economy will be focused. The legal status and the implementation process of international arbitration also be the discussing point of this paper.
Keywords: Business economy; Enforcement of awards; Globalization; International Arbitration

The UNCITRAL Model Law: "Follow you follow me" or "I do it my way" - Wilske, Stephan (Contemporary Asia arbitration Journal, 2025)
Keywords: Arbitral Awards; Arbitral procedure; Arbitration agreements; Arbitration friendliness; Domestic arbitration law; Germany; Harmonization; Harmonization of law; International Commercial Arbitration; International standards; Modernization; Recognition and enforcement; Statutory frameworks; Taiwan; UNCITRAL Model Law

The Middle Eastern and African Arbitration Review 2025 : Telecoms disputes in the Middle East and Africa - Mouzoula, Natalia; Kamau, Alice (Global Arbitration Review, 2025)

Social justice at the Commission for Conciliation Mediation and Arbitration (CCMA) and the critical role of the commissioner - Letlonkane, Katlego (Stellenbosch University, 2025)
ENGLISH ABSTRACT: This study provides exploratory insight into the social justice mandate of the Commission for Conciliation Mediation and Arbitration (“CCMA”) in the context of labour relations in South Africa. As a vehicle for the advancement of social justice through the efficient resolution of labour disputes, the CCMA is a compelling actor in the pursuit of social justice in South Africa’s labour environment. Social justice as a legislative and policy imperative requires an investment in understanding its conceptual ideals and demands in order to empower those acting in its pursuit with the knowledge they need to fulfil its demands. The CCMA’s most critical functionary, its commissioner, holds the key to unlocking labour justice for many members of the public. One wonders, given the criticality of advancing social justice in labour relations, whether social justice is appropriately understood in order to enable the kind of decision-making that efficiently and consistently addresses the workings of power and inequality as they manifest in employment relationships. This study’s main provocation is to transform the pursuit of social justice (in the South African labour context, at least) from an elusive endeavour to a more tangible, realistic one. It attempts to offer a way of thinking about and applying social justice in the practice of labour dispute resolution in South Africa and the CCMA context. It critically explores the interwoven mechanisms of power, prejudice, and injustice and how these mechanisms work to sustain unequal labour relations. The commissioner’s role is thus a critical one, that involves a deliberate pursuit to recognise, understand and interrupt these movements of power and mitigate the effect of inequality. Any movement towards social justice that does not pay close attention to this matrix of power and prejudice threatens to dilute the transformative potency of social justice. This study identifies and discusses the decisions of commissioners that fall short of the kind of conscientious decision-making required by a mandate of social justice. Discussions in this study also point out significant achievements in centralising social justice principles in decision-making processes at the CCMA, where arbitrators, in reducing injustice and advancing justice in labour relations, show a conscientious consideration and appreciation of historical contexts, power, privilege and disadvantage. Living up to the constitutional imperative to transform society in the way of equality, commissioners ought to develop their agency and be empowered by the Constitution of the Republic of South Africa, 1996, to disrupt inequality. This study contributes to the understanding and clarification of social justice and its implications for the South African labour environment. It also posits ubuntu as an important consideration in the balancing exercise required to achieve justice.
Keywords: Arbitration; CCMA; Commission for Conciliation, Mediation, and Arbitration; Dispute resolution (Law); Mediation; Mediation and conciliation, Industrial; Officials and employees; Social justice

Party autonomy and the applicable law to the merits in intellectual property arbitration - Rivoire, Maxence (Arbitration International, 2025)
The freedom of the parties to choose the applicable law to the merits is often presented as an important benefit of arbitrating disputes involving intellectual property (IP). Yet, the reality is more uncertain and controversial than is commonly assumed. Is party autonomy really permitted in IP arbitration? Should it be? This article answers these questions with regard to patents, trademarks, and copyrights, using recent examples drawn from arbitral practice. It first examines the situation where the parties only made a choice of contract law, and considers in this regard whether that law can and/or should be extended to infringement claims and/or the remedies to infringement, either directly or through the technique of characterization. After discussing the impact of overriding mandatory rules in contractual IP cases, the article then examines the situation where the parties chose a law to govern IP questions, including by way of a broad choice-of-law agreement covering non-contractual problems. It seeks to provide as much guidance as possible to arbitral tribunals, using mainly the distinction among infringement, ownership, and validity issues, and by distinguishing among different scenarios in which party autonomy is more or less acceptable.
Keywords: Arbitrage; Arbitragem; Arbitration; Intellectual property; Party autonomy

Transforming arbitration: exploring the impact of AI, blockchain, metaverse and Web3 - Piers, Maud; McCarthy, Sean (Radboud University Press, 2025)
In an era where technology is rapidly transforming the legal landscape, Transforming Arbitration explores how innovations like AI, blockchain, the Metaverse, and Web3 are reshaping arbitration as a key form of dispute resolution. The book features insights from leading academics, practitioners, and policymakers, offering a comprehensive look at how these advancements are influencing our conceptual, substantive and procedural understandings of many parts of this field. Each chapter examines the challenges and opportunities presented by these technologies, raising important questions about the compatibility of traditional arbitration processes with digital innovations. As the legal field adapts to developments like cryptocurrencies, NFTs, and 'virtual' disputes, this book provides valuable guidance on the future implications for arbitration. By questioning established norms and advocating for fresh approaches, Transforming Arbitration is a vital resource for legal professionals and scholars committed to evolving with the times. Combining theoretical exploration with practical recommendations, this collaborative volume equips the legal community with the tools to navigate the complexities of our digital age with confidence and foresight.
Keywords: AI; Arbitrage; Arbitragem; Arbitration; Artificial Intelligence; Blockchain; Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); Electronic Commerce; Inteligência artificial; Intelligence Artificielle; International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UNCITRAL Arbitration Rules; UNCITRAL Model Law on International Commercial Arbitration (1985)